When She Brings Home the Job Status: Wives’ Job Status, Status Leakage, and Marital Instability - Byrne, Alyson; Barling, Julian (Organization Science, 2017)
Women are increasingly represented in high status organizational positions. While the advancement of women into high status roles offers them many organizational benefits, the spillover and crossover effects of these high status positions on their marital relationships remain under explored. In this study, we focus on potential costs to the marital relationship when women in high status positions hold higher job status roles than their husbands. First, we examine the spillover effects of wives’ job status relative to their husbands’ on marital instability. We suggest that this relationship is indirect and mediated by negative thoughts and feelings toward their partners’ lower job status (which we refer to as “wives’ status leakage”) and decreased relationship satisfaction. Second, we investigate plausible crossover effects on husbands’ marital instability when wives have higher job status and suggest that husbands’ spousal support can moderate the indirect relationship between wives’ job status and wives’ marital instability. We explored these questions on 209 women in positions of high job status, a sample of 53 matched husband–wife dyads, and 92 of the wives who also completed questionnaires three years later. Full cross-sectional and longitudinal support emerged for the indirect spillover effects of wives’ job status on marital instability of wives, and direct crossover effects on husbands’ marital instability. In addition, the indirect relationship between wives’ job status on marital instability of wives was moderated by instrumental support. Theoretical contributions, practical implications, and future research suggestions are discussed. The online appendix is available at https://doi.org/10.1287/orsc.2017.1120 .